"Doing" Intergenerational Friendship: Challenging the Dominance of Age Homophily in Friendship. Issue 1 (22nd March 2021) - O'Dare, Catherine Elliott; Timonen, Virpi; Conlon, Catherine
ABSTRACT: This article challenges the dominance of age homophily in the literature on friendship. Using findings from a recent study on intergenerational friendship, we put forward a new conceptualization of a homophily of doing-and-being in friendships between adults who are of different generations. This research took a qualitative approach using constructivist grounded theory methodology. Homophily of doing-and-being has three components: being "friends in action" (pursuing interests and leisure activities, or simply spending time together), being "not only old" (sharing identities beyond age), and sharing attitudes and approaches to friendship and life. Additionally, "differences" were an important element of interest between the intergenerational friends. Our discovery of the centrality of doing-and-being, and the relative insignificance of age homophily, constitute a novel way of looking at friendship, and a new way of conceptualizing how and why (older) adults make and maintain friendships.